MEMPERTAHANKAN EKSISTENSI TRADITIONAL TRAVEL AGENCY DALAM MENGHADAPI ANCAMAN ONLINE TRAVEL AGENCY - Windya Anjastantri; Rizki Yudhi Dewantara (Jurnal Administrasi Bisnis, 2017)
Online travel agencies, with their own financial capability, not only making them daring to take the initial risk by investing on great magnitude of promotions, but also dare to lower the price extremely below the normal principle that others could not compete to it, which later becomes threat to the existence of traditional travel agencies that clearly not capable of providing the same benefit due to enormous operational cost. Therefore, competitive strategies are needed to maintain the existence of traditional travel agencies from the threatening online travel agency. The reasoning of competitive strategies regarding the threatened existence of traditional travel agency in this undergraduate thesis arranged based on the study of Terminaltiket. This research begins with analyzing both internal and external situations and formulated by using strategic industrial management approach along with three supporting tools, namely TOWS matrix, IE matrix and Grand Strategy Matrix. Furthermore, the qualitative and quantitative valuations of this research have been conducted by using AHP method. The final result of this research would be suggestion from the researcher to Terminaltiket as one of the traditional travel agencies to apply product development strategy in maintaining its existence. Keywords : Strategy management, competitive strategy, traditional travel agency ABSTRAK Online travel agency dengan kekuatan finansial mereka, bukan saja berani rugi terlebih dahulu dengan membiayai promosi besar-besaran, namun juga membanting harga dibawah prinsipalnya hingga tak mungkin ditandingi lagi, hal tersebut merupakan sebuah ancaman bagi eksistensi traditional travel agency yang tidak dapat memberikan potongan harga karena biaya operasional perusahaan yang besar. Maka dari itu, diperlukan sebuah strategi bersaing untuk dapat mempertahankan traditional travel agency dalam menghadapi ancaman online travel agency. Perumusan strategi mempertahankan eksistensi traditional travel agency pada skripsi ini mengambil studi pada perusahaan Terminaltiket. Penelitian ini didahului dengan menganalisis kondisi lingkungan eksternal dan internal. Perumusan strategi ini dilakukan melalui pendekatan manajemen startegi industry dengan menggunakan tiga buah alat bantu yaitu matriks TOWS, maktriks IE dan Grand Strategy Matrix. Pembobotan dan penilaian pada penelitian ini dikerjakan dengan metode AHP. Hasil akhir dari penelitian ini adalah peneliti menyarankan Terminaltiekt selaku Tradational Travel Agency untuk menggunakan strategi pengembangan produk untuk dapat mempertahankan eksistensinya. Kata kunci: Manajemen strategi, strategi bersaing, traditional travel agency